A template-free assembly of Cu, N-codoped hollow carbon nanospheres as low-cost and highly efficient peroxidase nanozymes. Issue 23 (31st October 2022) - Tao, Xian-Sen; Liu, Yuan; Gan, Ying; Li, Yue-Tong; Sha, Jingquan; Cao, An-Min
Abstract : Utilizing Cu 2+ -coordinated poly( m -phenylenediamine) as the precursor, Cu, N-codoped hollow carbon nanospheres as low-cost and highly efficient peroxidase nanozymes were assembled through a template-free strategy for the first time. Abstract : Developing carbon-based materials with high catalytic performance and sensitivity has significance in low-cost and highly efficient nanozymes. Herein, for the first time, Cu, N-codoped hollow carbon nanospheres (CuNHCNs) with highly active Cu-Nx sites were successfully assembled through a template-free strategy, in which Cu 2+ -poly( m -phenylenediamine) (Cu-PmPD) nanospheres were utilized as the source of Cu, N and C. Benefiting from the synergistic effect of the hollow spherical structure and optimized composition, the CuNHCN exhibits high affinity for 3, 3′, 5, 5′-tetramethylbenzidine and H2 O2 with 0.0655 mM and 0.918 mM, respectively, which are superior to those of HRP and most metal-based nanozymes. Moreover, by employing glucose and ascorbic acid (AA) as biomolecule models, a CuNHCN-based colorimetric detection platform is developed. The CuNHCN exhibits superior peroxidase mimicking activity and sensitivity in detecting glucose and AA with a detection limit of 0.187 μM and 68.9 nM (S/N = 3), respectively. Also, the colorimetric detection based on the CuNHCN towards glucose and AA in human serum presents superior practicability and accuracy. The assay provides a new avenue for designing and fabricating low-cost peroxidase nanozymes with high performance in bioassays.